Realitäten anerkennen, Rente zukunftsfähig gestalten - Martin Werding; Veronika Püschel; Benedikt Runschke; Milena Schwarz (Wirtschaftsdienst, 2024)
– Current plans to permanently fix the level of benefits provided by the German Statutory Pension Scheme are at odds with the reality of demographic ageing and the requirements for sustainable pension policies. Instead, the causes of the ageing process ought to be addressed through poten-tially unpopular reforms. Linking the statutory retirement age to further life expectancy and building up supplementary funded pensions are core elements of a far-sighted reform that could stabilise the German system of old-age provision in the long run. In the short run, increasing con-tribution rates and reducing the benefit level are inevitable. This should be communicated very clearly
Keywords: H55; J11; J26; 330; Gesetzliche Rentenversicherung; Deutschland; Gesetzliche Rentenversicherung; Deutschland